Applying a cognitive model to binge eating in a female community sample. - Young, E; Cooper, M (2013)
OBJECTIVE: Little is known about a potential cognitive model for binge eating, although cognitive behavioural techniques have been proposed as appropriate models of intervention. This study initiated the development of a cognitive model by applying an established cognitive model for bulimia nervosa. METHOD: A community sample of women was recruited via the internet and participants completed measures of eating disorder thoughts, negative self-beliefs, attachment, mood and binge eating severity. RESULTS: Eating disorder thoughts and negative self-beliefs were applicable to women in the community who binge eat. Attachment relationships characterised by decreased emotional warmth and increased overprotection, were correlated with binge eating in women and this relationship was mediated by eating disorder thoughts and negative self-beliefs. DISCUSSION: The cognitive model of bulimia was applicable to some extent to women in the community who binge eat. Attachment may also be related to binge eating and this relationship may be mediated by cognition.